CGIAR GENDER Impact Platform Newsletter, issue 2, June-July 2022 - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
In this issue, we share with you latest news from the CGIAR GENDER Impact Platform as well as updates on gender research from across CGIAR's research portfolio. This newsletter lessons from past crises that can help ensure an inclusive, gender-equitable response to today’s global food security emergency. We also highlight recent work to map climate–agriculture–gender inequality hotspots where climate hazards converge with large concentrations of women participating in food systems and significant structural gender inequalities, enabling investors to allocate scarce resources to most-at-risk populations. Updates from gender researchers across CGIAR include a roadmap for investors on how to mainstream gender-smart investing to scale climate-smart agriculture, a framework for gender-sensitive resilience interventions and a study in India that used storytelling to reveal who does what in wheat farming.